Premature aging of circulating T cells predicts all-cause mortality in hemodialysis patients - Xiang, Fangfang (BMC Nephrol, 2020)
BACKGROUND: Patients with end-stage renal disease (ESRD) exhibit a premature aging phenotype of immune system, which is recently concerned as a significant factor for increased risk of various morbidities. Nevertheless, there are few dates explicating the relevancy of T cell senescence to mortality. In this study, we prospectively studied the predictive value of T cell senescence for mortality in hemodialysis patients. METHODS: Patients who had been on hemodialysis treatment for at least 6 months were enrolled. T cell senescence determined by differentiation status was evaluated by flow cytometry. Survival outcomes were estimated using the Kaplan-Meier method. Univariate and multivariate analyses were performed to evaluate the prognostic impact of T cell premature aging and other clinical factors on all-cause mortality. RESULTS: A total of 466 patients (277 man and 169 women) were enrolled in this study. Decreased number of naïve T cell, as the most prominent feature of T cell senescence, did not change in parallel with age in these patients. Decreased absolute count of T cell, naïve T cell, CD4(+) naïve T cell were independently associated with all-cause mortality. Decreased percentage of T cell and increased percentage of CD8(+)central-memory T cell were also independently associated with all-cause mortality. After including all the T cell parameters in one regression model, only decreased count of naïve T cell was significantly associated with increased mortality in these patients. CONCLUSIONS: Aging-associated T cell changes are aggravated in ESRD patients. For the first time, our study demonstrates that naïve T cell depletion is a strong predictor of all-cause mortality in HD patients.